(untitled) (Nuntius Antiquus, 2017)
In this paper, I use Braga Bianchet’s model of Latin and her translation of Satyricon as tools to describe the causal chain from a theory of language to a linguistic model and from that model to our comprehension skills. In one route, I sketch an alternative description of Latin. In the other, I show how little explanatory power comes from Braga Bianchet’s claims. In the end, I extract a passage with a reference to a character’s body part in Braga Bianchet’s translation of Satyricon, then I demonstrate that any translator using her model of Latin would be lead to recognise an equivalent reference in the original. Finally, I show that such a miscomprehension does not happen when a translator uses a functional model of Latin such as the one sketched in this paper.